Antifungal Activity in Propolis Extracts Obtained in Jujuy, Argentina - Retamoso, Rosa Milagro (2019)
Propolis is a substance collected and produced by Apis mellifera from resins and buds vegetal. It has antifungal, antibacterial, antiviral and antioxidative activity. The objective of our work was evaluating in vitro activity of propolis extracts on the mycelium and spores of Aspergillus section Nigri and Penicillium chrysogenum series isolated from the cuticle of apiary-related ants. Propolis extracts from three localities in this province were used in this study. Spore germination inhibition was studied by means of immersion in propolis dilutions, whereas mycelium growth inhibition was observed by comparing fungal explants with those dilutions. Total flavonoid and phenolic contents in different extracts were evaluated. Significant differences were seen among propolis dilutions, being 0.3 and 0.03 g/mL concentrations the most effective ones. Propolis controls fungi coming from hive-related ants that may affect honey production.